Alcoholism : its treatments and mistreatments - Maltzman, Irving (World Scientific, 2008)
This important book provides a review of the Minnesota Model of alcoholism treatment, which combines current clinical treatments and the 12-step principles of Alcoholics Anonymous with the goal of abstinence. It critically examines the research base supporting cognitive behavior therapy approaches to alcoholism. Using evidence from biosociobehavioral science and critical analyses of alcoholism treatment outcome literature, the book rebuts the view of cognitive behavior therapists that "alcoholism is nothing but a bad habit". This book fills a vital need, describing which alcoholism treatments work and which do not. It is an invaluable guide to the helping professions caring for alcoholics, alcoholism counselors, social workers, nurses, clinical psychologists and psychiatrists as well as the intelligent layperson interested in alcoholism and its treatment. It also serves as a textbook for alcoholism courses and as an ancillary text for abnormal psychology courses.